Pengembangan Soal Higher Order Thinking Skills Pembelajaran Tematik Kelas VI Sekolah Dasar Negeri 39 Pontianak Kota - Arjuna Alina; Kartono Kartono; Siti Halidjah (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
This study aims to develop the higher-order thinking skills questions in thematic learning for grade VI of State Elementary School 39 Pontianak Kota. This research and development used Borg & Gall’s development model consisting of research and information gathering, planning, development of the initial product, initial field trials, main product revisions, field trials, and operational product revisions. Data were obtained from 16 students in Grade VI B and 30 students in Grade VI A. The data collection instruments were interview guidelines, questionnaires, and tests in the form of HOTS questions. Data were analyzed using the feasibility analysis of HOTS questions in terms of material, construction, and language aspects. The results of the study showed that the HOTS questions consisted of 20 multiple-choice questions. The feasibility of the materials in terms of material aspect obtained a value of 94% and was considered very feasible. The feasibility of the materials in terms of the construct aspect obtained a value of 95% and was considered very feasible. The feasibility of the materials in terms of the language aspect obtained a value of 94% and was considered very feasible. Thus, the developed product is considered suitable for use in the learning process.